¿Why should Perú stand for tele-education in times of covid-19? Opportunities and barriers for education. Challenges ahead - Ramos García, Yamil (2020)
Tele-education is a flexible remote teaching-learning modality, based on ICTs where the participants have elasticity in how, when and where to carry out the training action. It takes the same goals as its traditional equivalent and achieves the same teaching objective, learning achievement and professional competences so is considered the continuation of education. On the edge of COVID-19, Peru established a strict state of sanitary emergency and quarantine with strong regulations. In Education sector, lessons were suspended and the school year and educational facilities were closed. However, society showed the fracture of civility. Failure to comply with government regulations, misconduct in collective coexistence, health ignorance, social inequality, informality, crowds in markets, banks and public transport and homes with large families cause the multiplication of contagion. In this area, tele-education also implies the commitment of the educational process actors, students and teachers with appropriate environments and access to media, educational facilities with digital resources, capacities to analyze resources as well as thinking based on texts, images, audios and videos. Therefore, tele-education is shown as an effective and quality form of education to teach, protect and keep health, and it is shown as a valid and reliable way for education in times of COVID-19, thus maintaining educational services and continuing the development of individuals that contribute to the well-being and prosperity and the integral development of the person in society